The Use of Audiovisual Media in Learning Writing Persuasion Students Texts for VIII A Class MTsN 1 Mukomuko - Ersi Putri Nurfadillah. B; Irwan Satria; Vebbi Andra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
Activities to hone writing skills at MTsN 1 Mukomuko are still not widely implemented. In order to get students interested in writing learning activities using engaging learning materials, creative and innovative learning is required because they still struggle with writing skills and have poor writing structures. Audiovisual media is media that can display image and sound elements. The combination of these two elements is what makes audiovisual media have better capabilities. The purpose of this study is to identify the elements that encourage and discourage using audiovisual materials to teach writing persuasive essays. In order to make learning more successful, a variety of videos about persuasive text material are shown in the media. Additionally, because the media is very engaging for students, learning becomes more dynamic. This kind of study uses a qualitative descriptive method and is classified as qualitative research. Students in Class VIII A and Indonesian language teachers served as the research's subjects and informants. Techniques for gathering data included documentation, interviewing, and observation. Additionally, data reduction, data display, and conclusion-making are the steps in data analysis. The study's findings demonstrate how MTsN 1 Mukomuko's VIII A class has adopted the use of audiovisual materials to teach students how to create persuasive texts. Up till now, there has been an implementation of teaching persuasive text writing through audiovisual medium.